Congruous Torsional Down Beating Nystagmus in the Third Position of the Semont's Maneuver in Patients Treated for Canalithiasis of Posterior Semicircular Canal Benign Paroxysmal Positional Vertigo: Its Significance and Prognostic Value - Giannoni, Beatrice; Marcelli, Vincenzo; Verdolin, Ilaria; Checcucci, Curzio; Pollastri, Federica; Pecci, Rudi (Frontiers in Neurology, 2020)
Due to its mechanical pathogenesis, benign paroxysmal positional vertigo treatment is mainly physical: when posterior semicircular canal is involved, Semont’s maneuver is reported as one of the most effective liberating procedures. In the case of a canalolithiasis, the efficacy of the maneuver is corroborated by the appearance of some nystagmus findings during its performance. Liberating nystagmus, that can occur in the second position of Semont’s maneuver and whose direction is congruous with the excitation of the affected posterior semicircular canal has proven to be a favorable prognostic sign. On the other hand, in clinical experience, we’ve frequently verified the appearance of another nystagmus during the execution of the maneuver: upon reaching the third position, when re-placing the patient seated, a torsional down beating nystagmus, with the torsional component “congruous” with the stimulation of the vertical semicircular canals of the affected side, can often be appreciated. Such a sign can occur with or without having had the previous liberating nystagmus in the second position and is almost always associated with an intense vertigo and/or body pulsion. In this study we describe the incidence and characteristics of the congruous torsional down beating nystagmus that can arise by assuming the third position of Semont’s maneuver in a cohort of patients treated for posterior semicircular canal benign paroxysmal positional vertigo due to canalolithiasis. In the best of our knowledge, such a sign has never been described and explained before. On the basis of the pathophysiology and of the possible canal receptors stimulation during the different phases of Semont’s maneuver, we formulated different hypothesis on how such a nystagmus can be generated. We observed that such a sign, when elicited, has a very good prognostic meaning for healing purposes, even better than that of liberating nystagmus. Therefore, congruous torsional down beating nystagmus should always be checked when performing Semont’s maneuver because it could help in predicting success of physical treatment and in managing patients.